Heterologous amyloid seeding: revisiting the role of acetylcholinesterase in Alzheimer's disease - Jean, L; Thomas, B; Tahiri-Alaoui, A; Shaw, M; Vaux, D (Public Library of Science, 2007)
Neurodegenerative diseases associated with abnormal protein folding and ordered aggregation require an initial trigger which may be infectious, inherited, post-inflammatory or ideopathic. Proteolytic cleavage to generate vulnerable precursors, such as amyloid-β peptide (Aβ) production via β and γ secretases in Alzheimer's Disease (AD), is one such trigger, but the proteolytic removal of these fragments is also aetiologically important. The levels of Aβ in the central nervous system are regulated by several catabolic proteases, including insulysin (IDE) and neprilysin (NEP). The known association of human acetylcholinesterase (hAChE) with pathological aggregates in AD together with its ability to increase Aβ fibrilization prompted us to search for proteolytic triggers that could enhance this process. The hAChE C-terminal domain (T40, AChE575-614) is an exposed amphiphilic α-helix involved in enzyme oligomerisation, but it also contains a conformational switch region (CRS) with high propensity for conversion to non-native (hidden) β-strand, a property associated with amyloidogenicity. A synthetic peptide (AChE586-599) encompassing the CSR region shares homology with Aβ and forms β-sheet amyloid fibrils. We investigated the influence of IDE and NEP proteolysis on the formation and degradation of relevant hAChE β-sheet species. By combining reverse-phase HPLC and mass spectrometry, we established that the enzyme digestion profiles on T40 versus AChE586-599, or versus Aβ, differed. Moreover, IDE digestion of T40 triggered the conformational switch from α- to β-structures, resulting in surfactant CSR species that self-assembled into amyloid fibril precursors (oligomers). Crucially, these CSR species significantly increase Aβ fibril formation both by seeding the energetically unfavourable formation of amyloid nuclei and by enhancing the rate of amyloid elongation. Hence, these results may offer an explanation for observations that implicate hAChE in the extent of Aβ deposition in the brain. Furthermore, this process of heterologous amyloid seeding by a proteolytic fragment from another protein may represent a previously underestimated pathological trigger, implying that the abundance of the major amyloidogenic species (Aβ in AD, for example) may not be the only important factor in neurodegeneration.